2017
DOI: 10.1186/s40665-017-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and water availability: responses of alpine herb species along an elevation gradient

Abstract: Background: Alpine regions are particularly vulnerable to the effects of climate change. The Australian Alps are potentially more so than other mountain regions, as they cover a very small geographic area (<0.05% of mainland Australia), with a low maximum elevation (2228 m). Therefore, response to climate change will be primarily determined by the ability of species to survive in-situ through local adaptation or phenotypic plasticity. Existing climate change models project not only warming but increasingly var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…(2012) detected increased plant growth under 50% daylight and Geange et al . (2017) found that reductions in water addition of c . 25% are sufficient to induce plant trait plasticity.…”
Section: Methodsmentioning
confidence: 99%
“…(2012) detected increased plant growth under 50% daylight and Geange et al . (2017) found that reductions in water addition of c . 25% are sufficient to induce plant trait plasticity.…”
Section: Methodsmentioning
confidence: 99%
“…Key traits may relax the niche conservatism assumption by conferring the ability to colonize new habitats. For instance, underground plant-soil interactions (Goh et al, 2013;Sedlacek et al, 2014;Little et al, 2016) across different water levels (Geange et al, 2017) and cellular-anatomical physiological adaptations (Sandoval et al, 2019) may serve as pre-adaptations for a wider range expansion (Cuesta et al, 2017). Plastic traits may also broad the spectrum of novel climates (Arnold et al, 2019).…”
Section: Range Losses In the Espeletia Complex Will Widespread Througmentioning
confidence: 99%
“…Phenotypic plasticity of plants is the capacity for a given genotype to express different phenotypes under heterogeneous environments (Geange et al, 2017). Biomass allocation plasticity is a component of phenotypic plasticity, which is a mechanism for dealing with unpredictable environments.…”
Section: Introductionmentioning
confidence: 99%